2023
DOI: 10.7717/peerj.15639
|View full text |Cite
|
Sign up to set email alerts
|

Lp-PLA2 silencing ameliorates inflammation and autophagy in nonalcoholic steatohepatitis through inhibiting the JAK2/STAT3 pathway

Abstract: Background Nonalcoholic steatohepatitis (NASH), a common cause of liver-related morbidity and mortality worldwide, is characterized by inflammation and hepatocellular injury. Our research focuses on lipoprotein-associated phospholipase A2 (Lp-PLA2), an inflammation-related biomarker that has recently garnered interest in the context of NASH due to its potential roles in disease pathogenesis and progression. Methods We established a NASH mouse model using a high-fat diet (HFD) and treated it with sh-Lp-PLA2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…It has been reported that the inhibition of STAT3 activity could induce apoptosis and autophagy [ 14 , 15 , 16 ]. Apoptosis plays a key role in achieving cellular homeostasis and is characterized by chromatin condensation, cell shrinkage, and DNA fragmentation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the inhibition of STAT3 activity could induce apoptosis and autophagy [ 14 , 15 , 16 ]. Apoptosis plays a key role in achieving cellular homeostasis and is characterized by chromatin condensation, cell shrinkage, and DNA fragmentation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%